2021
DOI: 10.1038/s41578-021-00315-x
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional biomolecule nanostructures for cancer therapy

Abstract: Biomolecule-based nanostructures are inherently multifunctional and harbour diverse biological activities, which can be explored for cancer nanomedicine. The supramolecular properties of biomolecules can be precisely programmed for the design of smart drug delivery vehicles, enabling efficient transport in vivo, targeted drug delivery and combinatorial therapy within a single design. In this Review, we discuss biomolecule-based nanostructures, including polysaccharides, nucleic acids, peptides and proteins, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
203
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 317 publications
(204 citation statements)
references
References 255 publications
(320 reference statements)
0
203
0
1
Order By: Relevance
“…There are various types of proteins that have been used in nanoparticles such as serum albumin, ferritin, lipoproteins and virus-like particles. As an effective tool in targeted drug delivery systems, studies have revealed the great potential of natural proteins in targeting specificity, pH or stimulus-induced conformational changes to achieve sustained drug effects, drug stability and synergistic effects [ 30 , 31 ]. For example, Abraxane is a well-known albumin-bound nanoparticle of paclitaxel (PTX) for clinical use to combat cancer [ 32 ].…”
Section: Design and Fabrication Of Biomimetic Nanoparticlesmentioning
confidence: 99%
“…There are various types of proteins that have been used in nanoparticles such as serum albumin, ferritin, lipoproteins and virus-like particles. As an effective tool in targeted drug delivery systems, studies have revealed the great potential of natural proteins in targeting specificity, pH or stimulus-induced conformational changes to achieve sustained drug effects, drug stability and synergistic effects [ 30 , 31 ]. For example, Abraxane is a well-known albumin-bound nanoparticle of paclitaxel (PTX) for clinical use to combat cancer [ 32 ].…”
Section: Design and Fabrication Of Biomimetic Nanoparticlesmentioning
confidence: 99%
“…In the future study, accurate and programmable nanomaterial design principles are needed to allow tissue-specific macrophages' targeting, including the capability of dealing with the dynamic phenotype changing in the complicated biological environment. The conceptualization of nanorobots, [204] some of which could be AI-mediated or intelligent drug delivery, is a potential approach to deal with the complexity. Even within the same organ, it is necessary to distinguish the subphenotypes of different macrophages, including their embryonic origin.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…The clinical success of VYXEOS laid the foundation for more research of nanoparticle-mediated combination therapy to achieve synergistic therapeutic outcomes. In fact, the concept of co-delivery has been extended from combinations of two chemotherapeutic drugs to the co-delivery of chemotherapeutic drugs and gene therapy, immunotherapy, chemosensitizers or imaging agents for maximized therapeutic effects [46][47][48][49][50][51]. Furthermore, the ability to co-deliver therapeutic agents efficiently also proved to be effective in overcoming multidrug resistance (MDR) tumors [52,53].…”
Section: Current Trends and Potentials Of Nanomedicinesmentioning
confidence: 99%